INTERFERENSI MORFOLOGIS BAHASA BUGIS KE DALAM BAHASA INDONESIA PADA SISWA SMA NEGERI 1 TELLULIMPOE KABUPATEN SINJAI - NFN Tamrin (Multilingual, 2014)
When communicating, Indonesian people using Indonesian language as national language, besides their own regional one. Both languages sometimes use in oral and written. in their daily life. This situation lead to language interferention, the vocabulary of regional language may use into national and vice-versa. The aim of the study is describing the morfology interferention of Bugis language into Indonesia language which has been acted by the student of SMA Neg. 1  Tellulimpoe, Kabupaten Sinjai. The method applied is informal language.The informal arrangement are, apply the formula of common words by using dialogue, questionnaire, interview, observation, and recording technique. The data then are descriptively analysed. This step describe the situation and condition of the study data. The result of the study is : when communicating, the student of SMA Neg. 1 Tellulimpoe Kabupaten Sinjai do the interferention of Bugis into Indonesian language. The interferention of prefix is ta?- and the enclitique are –mi, -pi, –ji, -kik, –ko, -kak, and –ta.